Study on the liver Drug’s dominant metabolic enzymes for six effective components of the Huang qi Liuyi decoction - Wang, Qun; Tang, Tiantian; Wu, Zengguang; Yang, Hong; Gao, Yuan; Zhang, Shiyu; Song, Xinli; Chen, Xiaolan (Frontiers in Pharmacology, 2023)
Objective: To investigate the dominant metabolic enzymes of six effective components (astragaloside IV, glycyrrhizic acid, calycosin-glucuronide, formononetin, ononin, calycosin-7-O-β-D- glucoside) of Huangqi Liuyi decoction extract (HQD). Methods: Mouse liver microsomes were prepared. The effects of specific inhibitors of CYP450 enzymes on the metabolism of six effective components of HQD were studied using liver microsomal incubation in vitro. Results: The chemical inhibitors of CYP2C37 inhibit the metabolism of glycyrrhizic acid and astragaloside IV. Formononetin and astragaloside IV metabolism is inhibited by the chemical inhibitors of CYP2C11. The chemical inhibitors of CYP2E1 and CYP1A2 inhibit the metabolism of calycosin-glucuronide. Chemical CYP3A11 inhibitors prevent formononetin and glycyrrhizic acid from being metabolized. However, no inhibitor significantly affected the metabolism of ononin and calycosin-7-O-β-D-glucoside. Conclusion: CYP2C37 may be involved in the metabolism of astragaloside IV and glycyrrhizic acid, the metabolism of astragaloside IV and formononetin may be related to CYP2C11, the metabolism of calycosin-glucuronide may be related to CYP1A2 and CYP2E1, and CYP3A11 may be involved in the metabolism of glycyrrhizic acid and formononetin. This research provides an experimental basis for exploring the pharmacokinetic differences caused by metabolic enzymes.